Non-State actors and democratization process in Indonesia : have they lived to citizenry expectations? - Muyanja (CLACSO, 2021)
The objective of the research is to assess role(s) non state actors have played in Indonesian democratization process to date. The paper is explorative in nature, and uses multipronged qualitative research methodology. Techniques used to collect and analyze data included focused group discussion, in-depth interviews, literature review and content analysis. The coverage of the research is national and general in nature, with information sources drawn from academics and researchers, students activists, research papers, monographs, published reports, regulations that relate to the civil society activities, collaboration and cooperation in the realm of democracy, and central bureau of statistics and other relevant and reliable secondary data sources